Service providers on the move : labour mobility and the WTO General Agreement on Trade in Services (OECD Pub. ParisFR, 2003)
Defines and seeks to measure Mode 4 of the WTO General Agreement on Trade in Services (GATS). Looks at the treatment of labour mobility under regional trade agreements and examines the impact of Mode 4 and the options for progress in the current negotiations. Highlights the matter of recognition of qualifications.
Bibliography: p. 8